Sedimentologic Evidence For A Glacial Outburst Flood And Resulting Debris Flow; Puget Lowland, Washington State - Futornick, Z. O.; Goldstein, Barry S.; Parker, Brittany L.; Pringle, Patrick T. (Sound Ideas, 2008)
In the Puget Lowland of Washington State, recent evidence shows that several diamictons previously identified as glacial till are instead the result of a high-magnitude debris flow. Glacial deposits dominate much of the Puget Lowland and have been identified as mostly angular rocks of intrusive igneous and metamorphic origin transported from the north. However, several diamictons contain rounded to well-rounded andesitic Mount Rainier rock, indicating their source as the Lily Creek Formation and other andesite-bearing deposits of Mt. Rainier origin. Previously identified lacustrine deposits mapped by Crandell (1963), and other evidence within the Carbon River Valley on the western edge of the Cascade mountain range, support the fact that an ice-dammed lake rested there during the last glacial maximum, blocked by the Puget Lobe Ice Sheet. Radiocarbon dating shows that 100 years after the glacial maximum, about 16,850 years ago, the glacial terminus began to retreat (Porter and Swanson, 1998), releasing Glacial Lake Carbon and remobilizing the Lily Creek Formation, which is located in and near the mouth of the Carbon River Valley. This formation is identified by Crandell (1963) as a mid-Pleistocene debris flow which contains Mount Rainier lavas and pyroclastics. The event that remobilized the Lily Creek Formation is hypothesized by Pringle et al. (2000, 2002) and Goldstein et al. (2002) to have produced a high-magnitude debris flow which originated from the Carbon River Valley and deposited the diamictons as it traveled westward across western Washington. This research is centered on the Tanwax Lake and Eatonville, Washington quadrangles. Through field mapping and differentiation between debris flow, till, and outwash deposits, this study delineates an upstream pathway through which the debris flow would have traveled from east to west. No diamicton debris flow deposits have been seen north of 46 degrees 56'51"N or south of 46 degrees 50'7"N. Further analyses of the debris flow's grain size will present a likely ...